Zazulka - France, Anatole, 1844-1924.; France, Anatole, 1844-1924.; Nodier, Charles, 1780-1844.; Nodier, Charles, 1780-1844.; Nodier, Charles, 1780-1844.; Nodier, Charles, 1780-1844. (Warszawa : Votum, 1992)
Some children's stories by two noted French authors. Ages 8-12.